Auditor Reputation's Moderating Role in Intellectual Capital, Audit Committee Characteristics, and Earnings Management - Melani Caroline Olivia Sinaga; Made Gede Wira Kusuma (E-Jurnal Akuntansi, 2025)
The increase in company performance, followed by a decline in non-cyclicals consumer sector company profits in 2020–2022, it indicates that the corporation is using earnings management. The research objective is to empirically test the influence of intellectual capital and the audit committee on earnings management sector companies listed on the IDX in 2020-2022 which is moderated by auditor’s reputation. The sample of this research consisted of 65 companies with 196 observations. The results indicate intellectual capital has a significantly positive on management of earnings, the audit committee has a significantly negative on earnings management, and the reputation of auditors is unable to moderate the influence of intellectual capital and the audit committee on earnings management. The size of the company, used as a control variable, did not have a significant impact on earnings management. The practical implication is intellectual capital and audit committees can diminish the risk of earnings management.